Implementasi Algoritma Aes Rijndael 128 Pada Aplikasi Pengamanan Pengiriman Sms (Short Message Service) Berbasis Desktop - Mahmud Didi Nugraha; Safitri Juanita (KILAT, 2016)
Delivery secret information in a short message with SMS is not secure. This is case study research on UPT Pendidikan XII Kemang Bogor which is part of government intitution on education and culture of republic Indonesia which has responsibility for supervision business processes in public schools, one of the existing business processes in UPT are sending confidential information such as schedule unannounced inspections for supervisor ln public school without any security on the SMS, so easy to read by anyone. So, we need a security application in order for the SMS messages sent can be kept confidential. One way to secure the message is to use cryptographic, this technique wil encode message before sent (encrypt) and people who will receive message have to open message with key (decode). The algorithm used in this application is AES Rijndael algorithm 128. This application using system development life cycle Waterfall and using SMS Gateway features. Applications built using Java programming language and uses a MySQL database. Conclusion for this research is implementation AES Rijndael 128 algorithmto SMS security application can protect confidential information that is sent by operator to supervisor Education at UPT Kemang Bogor XIIwithout change message.